Remarks at the Opening Press Conference at World Bank/IMF Spring Meetings, Washington, D.C., April 14, 2011 - Zoellick, Robert B. (2016)
Robert B. Zoellick, World Bank Group President, addresses the biggest threat to the poor around the world: high and volatile food prices. The Bank released an updated Food Price Watch that underscores the need for the G20 to put food first. The key driver behind the upward spiral in the food price index has been sharp rises in the prices of wheat, maize, sugar, and oils. He discusses the global food price hikes which have pushed about 44 million people into extreme poverty. He focusses on global action to help small holder farmers, with seeds and fertilizer, better weather forecasting, better means to get produce to markets, also food and effective safety nets for the most vulnerable people. He concludes that we need global action to ensure we do a better job of feeding the hungry before we face the future challenges of feeding the expected nine billion people in the world in 2050. Zoellick fields questions on causes of the price hikes, measures needed in emerging market countries, a special Trust Fund Facility, Egypt and Tunisia, the longevity of the crisis, and civil problems in Libya.